2009
DOI: 10.1590/s1516-89132009000400026
|View full text |Cite
|
Sign up to set email alerts
|

Spray-drying of passion fruit juice using lactose-maltodextrin blends as the support material

Abstract: The objective of this study was to assess the effectiveness of the blends with different levels of lactose-maltodextrin (8:5, 10:5, and 12:5 % w/v) (180 and 190 °C), and two air pressures (0.10 and 0.20 MPa). The moisture content, hygroscopicity and vitamin C retention were evaluated in the powder obtained. Response surface plots (p<0.05) showed that the lowest values of the moisture content and hygroscopicity were reached in the temperature range of 188-190 °C and at 12:5 % (w/v) during the spray-dryi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 13 publications
4
21
2
4
Order By: Relevance
“…This variation is desirable, because it is within the range of quality parameters for a powder product to be considered a dry product. The results obtained by Angel et al (2009) were higher than the results found in the present study.…”
Section: Chemical Physical-chemical and Bioactive Compounds Analysescontrasting
confidence: 93%
See 2 more Smart Citations
“…This variation is desirable, because it is within the range of quality parameters for a powder product to be considered a dry product. The results obtained by Angel et al (2009) were higher than the results found in the present study.…”
Section: Chemical Physical-chemical and Bioactive Compounds Analysescontrasting
confidence: 93%
“…Certainly, a fact to be considered to explain the observed behavior is the presence of maltodrextrin in powder form which is considered to be a substance of low hygroscopicity. Angel et al (2009) when studying the passion fruit powder obtained by spray drying, observed values of 17.39 to 35.38 g of absorbed water/100 g and concluded that the passion fruit powder was more hygroscopic due to the presence of lactose and fructose (main monosaccharide present), present in amorphous state, and is not stable in the normal moisture.…”
Section: Chemical Physical-chemical and Bioactive Compounds Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The values were much lower than those found by Angel et al (2009), in a study on spraydrying of passion fruit juice using maltodextrin and lactose as drying adjuvants, who found higroscopicity values between 17 and 35%. Soursop pulp powder with 15% of maltodextrin showed significant statistic differences when compared to the values of the other powders, but it maintained the same classification (Table 4).…”
Section: Resultscontrasting
confidence: 62%
“…They determined the T g of inulin by MDSC and reported a value of 125°C. With the same purpose, Ruiz et al (2009) employed a mixture of lactose-MX for the spray drying of passion fruit juice without sticking problems (Ruiz et al, 2009). Additionally, Saavedra et al (2015) reported the T g in the range of 52-100°C of a set of MXs with different DE and DP (Saavedra et al, 2015).…”
Section: Setting the Spray Drying Conditions Based On The T G Of The mentioning
confidence: 99%